Analisis Hukum Terhadap Pembinaan Anak Pidana Di Lembaga Pembinaan Khusus Anak Kelas I Medan - Silalahi, Andre; Marlina, Marlina; Eddy, Triono; Nasution, Aulia Rosa (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
This study aims to examine how the process of fostering criminal children is carried out by the Special Class Fostering Agency for Children in Medan, what are the obstacles faced in the implementation of fostering of criminal children and how the efforts made to overcome the problems of fostering criminal children in the Class I Special Guidance Institution . This research is normative juridical legal research and also empirical or sociological legal research, which examines library materials relating to the fostering of criminal children in the Class I Special Child Development Institute (LPKA) Medan. It was found that fostering prisoners and students is a heavy and noble task, not everyone is able and interested in the life of prisoners. And there are regulations and the fostering process for criminal children in Class I Special Guidance Institutions in Medan. The obstacles faced in the implementation of coaching activities in the Special Guidance Institution for Class I Children in Medan are originated from the factors of education, coaches, motivation and facilities and infrastructure; While the efforts made to overcome these obstacles include making improvements including aspects of education, coaches, motivation, and facilities and infrastructure.